Environmental enrichment facilitates cocaine‐cue extinction, deters reacquisition of cocaine self‐administration and alters AMPAR GluA1 expression and phosphorylation. (18th September 2015) - Gauthier, Jamie M.; Lin, Amy; Nic Dhonnchadha, Bríd Á.; Spealman, Roger D.; Man, Heng‐Ye; Kantak, Kathleen M.
Abstract: This study investigated the combination of environmental enrichment (EE) with cocaine‐cue extinction training on reacquisition of cocaine self‐administration. Rats were trained under a second‐order schedule for which responses were maintained by cocaine injections and cocaine‐paired stimuli. During three weekly extinction sessions, saline was substituted for cocaine but cocaine‐paired stimuli were presented. Rats received 4‐h periods of EE at strategic time points during extinction training, or received NoEE. Additional control rats received EE or NoEE without extinction training. One week later, reacquisition of cocaine self‐administration was evaluated for 15 sessions, and then GluA1 expression, a cellular substrate for learning and memory, was measured in selected brain regions. EE provided both 24 h before and immediately after extinction training facilitated extinction learning and deterred reacquisition of cocaine self‐administration for up to 13 sessions. Each intervention by itself (EE alone or extinction alone) was ineffective, as was EE scheduled at individual time points (EE 4 h or 24 h before, or EE immediately or 6 h after, each extinction training session). Under these conditions, rats rapidly reacquired baseline rates of cocaine self‐administration. Cocaine self‐administration alone decreased total GluA1 and/or pSer845GluA1 expression in basolateral amygdala and nucleus accumbens. Extinction training, with or without EE, opposed these changes and also increased total GluA1 in ventromedial prefrontal cortex and dorsal hippocampus. EE alone increased pSer845GluA1 and EE combined with extinction training decreased pSer845GluA1 in ventromedial prefrontal cortex. EE might be a useful adjunct to extinction therapy by enabling neuroplasticity that deters relapse to cocaine self‐administration. Abstract : Brief 4‐h periods of environmental enrichment (EE) scheduled both 24 h before and immediately after weekly cocaine‐cue extinction training significantly facilitated the rate of extinction learning and deterred reacquisition of cocaine self‐administration. EE alone or extinction alone was ineffective, as was EE scheduled at individual time points. The combination of EE with extinction training altered pSer845GluA1 expression in both the ventromedial prefrontal cortex and the basolateral amygdala. Thus, EE might be a useful adjunct to extinction therapy by enabling neuroplasticity that deters relapse to cocaine self‐administration.